Enabling the fabrication of complex soft iontronics using multi-material 3D extrusion printing - Kalkus, Trevor; Unterreiner, Tamara; Schmidt, Målin; Wächter, Laura D.; Schmitt, Christina R.; Mishra, Ankit; Selhuber-Unkel, Christine (Advanced science, 2025)
Iontronics can improve soft robotics, including wearable devices and environmental sensors, by replacing rigid electronics with viscoelastic materials that mimic biological tissue. Circuit components have been fabricated with soft materials that utilize ionic current, but the process can be tedious and widely applicable manufacturing methods are lacking, hindering the development of complex iontronic circuits for real-world applications. With multi-material 3D printing, this work demonstrates the ability to rapidly iterate ionic diode design and integrate these diodes within complex structures with biomimetic mechanical behavior. Print quality and material properties can be tuned by adjusting the concentration of the ink's components. To emphasize the rapid iteration enabled by 3D printing, a library of the ionic diodes with varying sensitivity to strain is evaluated. The utility of these ionic diodes is demonstrated by integrating them within logic circuits that respond to mechanical cues and demonstrate bio-inspired strain-stiffening behavior. These devices are functional directly from the 3D printer, are extremely flexible, and can be submerged in water without losing functionality. The adaptability afforded by multi-material extrusion printing make it an ideal candidate for enabling the next generation of iontronics capable of advanced computational and mechanical functionality.